Modification of pyridine-terminated aromatic self-assembled monolayers by electron irradiation - Yildirim, Can; Sauter, Eric; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
Using a series of model systems, we studied the effect of electron irradiation on pyridine-terminated aromatic thiolate self-assembled monolayers (SAMs) on Au(111). All these SAMs exhibited behavior similar to that of oligophenyl-based films, viz. a progressive and extensive cross-linking, preventing release of individual molecules and their fragments and slowing down and hindering the damage of the SAM/substrate interface. The pyridine moieties participated in the formation of the cross-linking network, which was accompanied by their chemical modification and partial hydrogenation. As a consequence, the nitrogen content in the films did not change significantly upon irradiation (only ∼10% for the densely packed SAMs) and the modified pyridine moieties became reactive toward carboxylic acid anhydrides. The extent of irradiation-induced modification and damage was found to depend strongly on the structural quality and packing density of the monolayers. The results of the experiments suggest several potential applications of pyridine-terminated aromatic SAMs in context of their modification by electron irradiation, in the framework of conventional and chemical lithography as well as advanced nanofabrication.
Gesehen am 03.07.2018